Estimate of a nonflow baseline for the chiral magnetic effect in isobar collisions at RHIC - Feng Yicheng (EPJ Web of Conferences, 2023)
Recently, STAR reported the isobar (4496Ru + 4496Ru, 4096Zr + 4096Zr4496Ru+4496Ru, 4096Zr +4096Zr) results for the chiral magnetic effect (CME) search. The Ru+Ru to Zr+Zr ratio of the CME-sensitive observable Δγ, normalized by elliptic anisotropy (υ2), is observed to be close to the inverse multiplicity (N) ratio. In other words, the ratio of the NΔγ/υ2 observable is close to the naive background baseline of unity. However, nonflow correlations are expected to cause the baseline to deviate from unity. To further understand the isobar results, we decompose the nonflow contributions to NΔγ/υ2 (isobar ratio) into three terms and quantify each term by using the nonflow in υ2 measurement, published STAR data, and HIJING simulation. From these studies, we estimate a nonflow baseline of the isobar ratio of NΔγ/υ2 for the CME and discuss its implications.